Integrated control of Chagas disease for its elimination as public health problem--a review - Sosa-Estani, Sergio (2015)
Fil: Sosa-Estani, Sergio. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.